The Autonomous Technical Institutes:The Way Ahead - Waghodekar, P. H. (Journal of Engineering Education Transformations, 1994)
The present Technical and Management Education System in India can be considered as an extension to the pre-independence education system designed by the British rulers. It is controlled either by the Government or semi-Government organisations, like universities. The demand for professional education is rising very sharply, and the Government, because of its limited financial and managerial capabilities, is not in a position to cope up with such demand. It is, therefore, proposed that full autonomy in the areas of academic, administrative and financial matters ought to be granted, rather than in a piecemeal fashion, to technical institutes. Some aspects of autonomy have been presented. For example, the autonomous institute management maturity grid and the concept of SEFI have been advocated.